10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Late vitamin K deficiency bleeding should be considered in exclusively breastfed infants presenting with seizures, pallor, or unexplained bleeding, particularly when vitamin K prophylaxis was not administered at birth. Early diagnosis and prompt vitamin K administration can rapidly correct coagulopathy and prevent life-threatening intracranial hemorrhage.